The Use of Retinoids in Ovarian Cancer: A Review of the Literature. Issue 2 (1st February 2012) - Whitworth, Jenny M.; Straughn, J. Michael; Atigadda, Venkatram R.; Muccio, Donald D.; Buchsbaum, Donald J.
Abstract : Abstract: Ovarian cancer is the deadliest of all gynecologic malignancies. The search for novel treatment modalities to augment traditional chemotherapy and improve quality of life is ongoing. Retinoids, a class of compounds composed of vitamin A, its natural derivatives, and synthetic analogs, have been studied extensively in both the prevention and treatment of gynecologic malignancies. In this article, we reviewed preclinical studies and clinical trials conducted using retinoids in ovarian cancer.